Metabolic Syndrome: Inflammatory Mechanisms Obesity Insulin Resistance and Depression - Kreeinthong, Sukanya; Mongkol, Sarayoot; Sookkua, Tichaporn; Sonpeayung, Rattanaporn (Journal of health and health management, 2025)
Metabolic syndrome (MetS) is a cluster of interrelated metabolic disorders, including central obesity, hypertension, dyslipidemia, and insulin resistance. Its development is influenced by genetic predisposition, lifestyle behaviors, and chronic low-grade inflammation. A key pathological mechanism involves inflammation initiated by adipose tissue, which secretes pro-inflammatory cytokines such as leptin and tumor necrosis factor-alpha (TNF-α), thereby impairing insulin sensitivity and contributing to the progression of MetS. Additionally, MetS is associated with autonomic nervous system dysfunction, which can be evaluated through reduced heart rate variability (HRV). Furthermore, it is linked to depressive symptoms that arise from physiological changes, emotional stress, and negative self-perception, with inflammation identified as a common underlying factor. Current scientific evidence supports that physical activity, when prescribed according to the FITT principle (frequency, intensity, time, and type) particularly aerobic exercises such as brisk walking, running, swimming, and traditional Thai dance (Ram Wong)—is effective in mitigating the risk of MetS, improving autonomic function, and reducing depressive symptoms. Therefore, a holistic health promotion strategy involving the active participation of healthcare professional and individuals, is essential for the effective prevention and long-term management of metabolic syndrome.